(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
This research focused on the implementation of Open MP. It considers the parallelization of an application code that simulates the thermal gradient of material in two dimensions. A ‘C language’ program code called jacobi2d.c that solves a rectangular 2-dimensional heat conductivity problem using Jacobi iterative method was used. The boundary conditions required to compute a temperature distribution for a rectangular 2D problem are: Top 300C, Bottom 500C, Left 400C and Right 900C with a range of problem sizes enter as a run-time parameter to alter the problem sizes and convergence criteria. Also, there were computations and readings for iterations and runtime for four values of M and N which were selected for 01, 02, and 03 optimizations. In Table 1 Readings, four values were selected for each of the iterations. The results show the performance of the runtime as the processor increases from 01-optimization, to 02-optimization and finally to 03- optimization. It can be deduced from the representation that the run time of the values reduces as more resources are allocated to execution through the increase in optimization level. Also, in Table 2 Readings, the runtime decreases as it moves from thread1, thread2, thread3, and thread4, comparing the last values for thread1 which are M is 180, N is 200, and their runtime which is 42.797187001. Also the last values for thread2 which are M is 180, N is 200, their runtime which is 21.772106003. When the two runtimes were compared, it was discovered that there was a decrease in the runtime because the more the thread increases, the more system resources they share such as a processor which may affect their runtime by increasing it.